Sharing the Responsibility: CSR and the Interative Roles of Agency Groups. - S'Agostino, Thomas Anthony (2008)
This paper addresses the concept of Zones of Responsibility and the interaction between key agency groups regarding the Greenhouse Debate. Focus is given to four key agencies: Corporate Business, Government, Accountancies, and The General Public, with the perceived responsibilities of each group explored in relation to one another. The paper explores these interactive dynamics by means of qualitative and quantitative research, and by way of a Case Study examination of the Kingsnorth Power Facility and the subsequent CCS debate. It ultimately concludes with the inadequacies perpetuated by the current system of reliance, with the agency relationships summated through a Model of Dependent Agency. The model raises questions, and offers a potential silver lining to the Environmental CSR dilemma in the UK.